Realization of free space optics with OFDM under atmospheric turbulence - Chaudhary, Sushank; Amphawan, Angela; Nisar, Kashif (Elsevier Ltd., 2014)
Free space optics (FSO) technology provides a promising solution for future broadband networks, offering high data transmission compared to RF technology. This work is focused on investigating the performance of an FSO system with OFDM and QAM. A 10 Gbps data stream is transmitted using a 4-level QAM sequence through the FSO system under different atmospheric conditions. Results indicate that the integration of SOA prolongs the maximum achievable distance with acceptable SNR to 185 km under clear weather conditions whereas under atmospheric fog, the maximum distance is extended to 2.5 km